2011
DOI: 10.1002/asi.21643
|View full text |Cite
|
Sign up to set email alerts
|

Everyday appropriations of information technology: A study of creative uses of digital cameras

Abstract: Repurposive appropriation is a creative everyday act in which a user invents a novel use for information technology (IT) and adopts it. This study is the first to address its prevalence and predictability in the consumer IT context. In all, 2,379 respondents filled in an online questionnaire on creative uses of digital cameras, such as using them as scanners, periscopes, and storage media. The data reveal that such creative uses are adopted by about half of the users, on average, across different demographic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 72 publications
0
16
1
Order By: Relevance
“…In addition to the intended, designed uses of mobile devices, earlier research has also identified more improvised repurposive use, for example, using a mobile phone (with a camera) as a mirror, a periscope, a tool for note taking or an instruction device (Salovaara et al, 2011), none of which require an active phone subscription or access to mobile data connectivity. Mobile apps offer additional functionality that goes well beyond the original communicative purposes of the device, for instance, the flashlight app.…”
Section: The Evolving and Dissolving Mobile Artefactmentioning
confidence: 99%
“…In addition to the intended, designed uses of mobile devices, earlier research has also identified more improvised repurposive use, for example, using a mobile phone (with a camera) as a mirror, a periscope, a tool for note taking or an instruction device (Salovaara et al, 2011), none of which require an active phone subscription or access to mobile data connectivity. Mobile apps offer additional functionality that goes well beyond the original communicative purposes of the device, for instance, the flashlight app.…”
Section: The Evolving and Dissolving Mobile Artefactmentioning
confidence: 99%
“…Salovaara et al surveyed the creative uses of conventional digital cameras [5]. Based on data from 2000 users, they report that half (48%) of the users employ, or are aware of, some ways of creative use in this domain.…”
Section: Introductionmentioning
confidence: 99%
“…as a mirror or scanner. In contrast to [5], which looked at the use of digital cameras in general, we concentrate on functional photos taken with a cameraphone. Our research differs from [5] in the following aspects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations